PEMANFAATAN TEKNOLOGI E-COMMERCE DALAM PROSES BISNIS - Edwin Agung Wibowo (EQUILIBIRIA, 2014)
Electronic Commerce (e-commerce) is the process of buying, selling or exchanging products, services and information via computer networks. ecommerce is part of the e-business, where the scope of e-business more broadly, not just commercial but also include business partners, customer service, job vacancies. In addition to networking technologies www, e-commerce technology also requires a database or a database (database), e-mail or electronic mail (email), and the form of non-computer technology as well as other delivery systems, and means of payment for e -Commerce. Given the electronic commerce (ecommerce) is then the customer can access and perform orders from various places. Given the current era of advanced technology is the customer who wants to access e-commerce does not have to be somewhere, it is because in the big cities in Indonesia have a lot of places that provide an internet access facility using only the laptop / notebook or by Personal Digital Assistant (PDA) using wifi technology. Thus the time is now very necessary and desirable companies to implement e-commerceservices. The use of e-commerce in Indonesia is still very limited. From the background that there is then the author will discuss how ecommerce pemanfaaatan in their business interests.